Effect of high oxygen deficiency in nano-confined bismuth sesquioxide. (29th April 2020) - Sanna, Simone; Firodaliso, Elisabetta Maria; Kasama, Takeshi; Castelli, Ivano E; Esposito, Vincenzo
Abstract: Bismuth sesquioxide in its cubic form, i.e. δ -Bi2 O3, is the fastest oxygen ionic conductor known which has important applications in energy technologies. However, the material is unstable as it undergoes high-density polymorphic transitions and degradation. In this work, we show that δ -Bi2 O3 can be stabilized both at high and low temperatures (T < 775 °C) under low oxygen partial pressure (pO2  < 10 −5 atm), where the material is nanostructured in multilayered thin film coherent heterostructures with yttrium stabilized zirconia. Density Functional Theory calculation confirms such a form of metastability, also showing that high oxygen defect concentration favors the cubic phase. Moreover, high oxygen deficiency in the nanoionics leads to an unexpected 'two-regime' conductivity with high values ( σ  > 1 S cm −1 at 600 °C) at high pO2 and lower ionic conductivity ( σ  ∼ 0.1 S cm −1 at 600 °C) at low pO2 . Ionic conductivity at low pO2 occurs with high activation energy (Ea > 1.5 eV), suggesting a drastic decrease in mobility for high concentration of defects.